Cultura organizacional y desempeño laboral en los colaboradores de la cooperativa de ahorro y crédito Sumak Kawsay Ltda.” - Silva Montaguano, Michelle Alexandra (2024)
Organizational Culture is considered as a set of factors that guide behavior and define how people work in their work environment. In addition, it plays a critical role in employee satisfaction, motivation, commitment, and retention. The main objective of this research was to establish the relationship between organizational culture and the work performance of the employees of the Cooperativa de Ahorro y Crédito Sumak Kawsay Ltda. A cross-sectional correlational design methodology was used, with a quantitative approach to collect and analyze the data obtained, for its processing the statistical software called "Statistical Package for Social Sciences" (SPSS) was used, where the results revealed that there is a high relationship between organizational culture and work performance, through Spearman's correlation it was evidenced that the value of 0.585 reflected between the Norms-Responsibility dimension, the value of 0, 677 between Creating change-Attitude of service indicate that there is a moderate correlation, while the value of 0.774 between Involvement with the purpose-Communication, the value of 0.717 between Customer focus-Attitude of service, the value of 0.702 between Teamwork-Communication and the value of 0.711 between Search for social welfare-Communication indicate that there is a high correlation, however the dimension of identity projected negative data indicating that there is a null correlation with performance. Consequently, through simple linear regression, the strength of the effect of norms, involvement with the purpose, creation of change, customer focus, teamwork, and search for social welfare on performance was determined, concluding that as the organizational culture is strengthened, it tends to increase the performance of the collaborators. Finally, strategies that contribute to its improvement were developed.